Mahathir's Pacific solution - Journeyman Pictures (United Kingdom : Journeyman Pictures, 2003)
For 20 years Dr. Mahathir Mohamad has critised Australia essentially as being an outpost of Western paternalism in a region determined to throw off its colonial past. That's a message that resonates in Papua New Guinea at the moment where many local politicians fear that Australia is seeking to regain control. This video reports on the messages Dr. Mahathir Mohamad had to deliver before his retirement when his pointedly travelled to Papua New Guinea
Title from container
Keywords: Mahathir Mohamad, -- Tun, -- 1925-; Political science; Politicians; Colonies